Abertura em mulheres lésbicas e suas implicações para a saúde mental, acesso ao serviço de saúde e prevenção sexual e reprodutiva - Silveira, Aline Pompeu (2019)
Disclosure of sexual orientation in lesbian women has been associated in the scientific literature with aspects concerning their physical, mental, sexual and reproductive health, and is directly related to the occurrence of comprehensive care in health services. Despite its great relevance, outness is not a concept recurrently used in Brazilian and / or portuguese-written research. Gathering scientific evidence that demonstrates the importance of disclosure to health care for lesbian women can serve as a basis for guidance documents directed to health professionals to broaden the scope and quality of care provided. Thus, the present study proposed an investigation into the influence of outness on the health of lesbian women in the Brazilian context. To this aim, two studies were conducted: An integrative literature review on outness and its implications for the health of lesbian women and a second quantitative study, which aimed to observe how the outness variable relates to mental health, access to health care services and sexual and reproductive prevention of lesbian women in the Brazilian context. It is argued that outness in lesbian women is determined by sociodemographic factors. In addition, outness interferes with lesbian women's access to health services, as well as the quality of care, which therefore affects their sexual and reproductive prevention.